Circular tubes for fluids in aluminium and aluminium alloys. Diameter 3, 2 mm ≤ D ≤ 100 mm. Thickness 0, 6 mm ≤ a ≤ 2, 5 mm. Dimensions. (15th June 1997) - British Standards Institution,
No abstract available